ТHE WAYS OF IMPROVEMENT OF LIVING STANDARDS - Muminov, Nozim (International Journal of Psychosocial Rehabilitation, 2020)
The article explores the conceptual foundations of the standard of living of the population and the system of needs; the mechanisms of the relationship between incomes and living standards of the population are determined through a number of factors and its changes are investigated; The causes of poverty, factors, indicators of its determination, regional aspects and effective methods of poverty reduction were identified; the state, trends and directions of improving the human development index are identified; the necessity of calculating the integral index of increasing social welfare of the population is justified; priority areas of the strategy for improving the living standards of the population have been developed. The obtained scientific proposals and practical recommendations can be used to improve the legislative framework for raising the living standards of the population, developing a strategy to improve the living standards of the population and targeted social programs.